Experimental study on damping properties of concretes under free vibration with different tyre wastes - Cho Zin Win; Khin Su Su Htwe; Nyan Myint Kyaw (Researcher and Lecturer Society, 2025)
Disposing of waste tires presents environmental challenges, making recycling into crumb rubber a sustainable solution, especially in developing countries. Moreover, concrete tends to be brittle, and incorporating crumb rubber enhances its energy absorption, which can help reduce the concrete’s brittleness. This study examines the effects of replacing fine aggregates with crumb rubber at 5% and 10% on concrete properties. Two types of crumb rubbers were used namely, low-quality and high-quality crumb rubber treated with CH3COOH solution. Results show that 5% crumb rubber improves compressive strength, and elastic modulus, while these properties decrease at 10% replacement. Free vibration tests using the logarithmic decrement method showed that higher rubber content increases the damping ratio, with 10% replacement yielding the best energy dissipation. Simulation using ANSYS Workbench validated the experimental findings, with natural frequencies and load-displacement behaviors closely matching experimental results. Using 5% crumb rubber enhances compressive strength, damping, and energy absorption, making concrete more versatile. This eco-friendly alternative supports sustainable construction while addressing tire waste disposal, highlighting its potential for dynamic load applications.